Keterlibatan Orang Tua Bersama Guru dalam Mendukung Proses Pembelajaran Anak Usia Dini di TK Kristen Rajawali Sakti 3 Palangka Raya - Zefanya Octoberi; Natali Purwanti; Nanda Amelia; Cailla Yovanca F; Hartani Hartani (Educational Journal, 2026)
Parental involvement is an important factor in supporting the learning process of early childhood. This study aims to describe the forms of parental involvement with teachers in supporting the learning process and to identify the forms of cooperation and communication established between parents and teachers at TK Kristen Rajawali Sakti 3 Palangka Raya. This research employed a qualitative approach with a case study design. The participants consisted of teachers, parents, and the principal who were selected purposively. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that parental involvement is manifested through participation in school activities, assistance in children's learning at home, provision of learning facilities, and monitoring of children's development. In addition, cooperation between parents and teachers is carried out through regular communication, meetings, and discussions regarding children's learning and developmental progress. The collaboration established between parents and teachers contributes positively to creating continuity between home and school learning environments, thereby supporting children's holistic development. Therefore, strengthening partnerships between families and schools is essential to optimize early childhood learning processes.